Identification of Priority Areas for the Conservation of Stream Fish Assemblages: Implications for River Management in France. (16th October 2016) - Maire, A.; Laffaille, P.; Maire, J.‐F.; Buisson, L.
Abstract: Financial and human resources allocated to biodiversity conservation are often limited, making it impossible to protect all natural places, and priority areas for protection must be identified. In this study, we applied ecological niche models to predict fish assemblages in the stream network of France. Four non‐correlated conservation objectives were derived from these species assemblages: taxonomic diversity, functional diversity, natural heritage importance and socio‐economic value. We proposed a multi‐objective prioritization method based on the Pareto optimality principle to rank the planning units (i.e. 6097 subcatchments) according to their inherent trade‐offs between the four conservation objectives. Four types of hydrosystems of great conservation importance presenting specific fish assemblages were identified: (i) the most upstream areas of large catchments; (ii) the most downstream areas of large catchments; (iii) the small coastal catchments of the English Channel and the Atlantic Ocean; and (iv) the Mediterranean streams of medium altitude. The fish assemblages characterizing these hydrosystems were complementary and representative of the entire fish fauna of France. Most of these priority subcatchments were found to be practically suitable for the implementation of conservation actions, which is very promising for the protection of river biodiversity. Copyright © 2016 John Wiley & Sons, Ltd.